Alcohol Relapse After Liver Transplantation: Risk Factors, Outcomes, and a Comparison of Risk Stratification Models - Karen Young; Yuval A. Patel; Benson Hoffman; Sarah Peskoe; Shein-Chung Chow; Karli Erhart; Jennifer Jackson; Stephanie Garbarino (Gastro Hep Advances)
Background and Aims: Alcohol-related liver disease is a leading cause of liver transplantation (LT) in the United States; however, alcohol relapse remains a risk, and real-world assessment of relapse prediction scores is lacking. The primary aim of this study was to assess risk factors for alcohol relapse and compare effectiveness of pre-existing risk scores (e.g., Sustained Alcohol Use Post-Liver Transplant (SALT) and Harmful Alcohol Use Post-Liver Transplant (HALT) scores). Methods: This was a retrospective chart review of 69 adults who underwent LT for alcohol-related liver disease at Duke University Hospital from January 1, 2018, to January 1, 2021. Outcome variables included relapse post-LT, severity of relapse, and graft dysfunction. Results: Sixty-seven patients with a median follow-up time of 43 months were included. Eighteen (27%) experienced alcohol relapse. Of those, 16 (89%) had heavy alcohol use and 3 of those patients (17%) experienced graft dysfunction. Factors significantly associated with relapse included younger age, prior relapse, significant psychiatric comorbidities, alcohol use after cirrhosis diagnosis, shorter abstinence before LT listing, and prior alcohol treatment program. When applying SALT and HALT scores, the area under the curve was 0.69 (95% confidence interval 0.53–0.85) and 0.66 (95% confidence interval 0.50–0.81), respectively. Conclusion: In our cohort, heavy alcohol use before transplantation and legal issues did not predict relapse, which are common components of prediction scores. Less than 5% of patients had graft dysfunction due to relapse, suggesting good graft outcomes. While the HALT and SALT scores were validated in our cohort, our finding of additional significant predictors of relapse, in addition to previously reported risk factors providing protective effect, suggests opportunity for further optimization of prediction scores.